Pengaruh Inflasi Dan Bi Rate Terhadap Penyaluran Kredit Di Provinsi Jambi - Dani, Rian; Wiarta, Iqra; Tri Kurniasih, Endah; Armandito (Brida Provinsi Jambi, 2025)
Regional Development Banks have an important intermediary function in supporting regional development. Credit distribution to the community will improve community welfare. This study aims to analyze the influence of macroeconomic variables, namely inflation and Bank Indonesia interest rates on the development of credit distribution at the Jambi Regional Development Bank (Bank Jambi). The quantitative descriptive research method is used to answer the problems raised in this study with secondary data for the period 2020 to 2023. The analysis tool in this study is multiple linear regression. The results of the study show that the development of credit distribution at Bank Jambi is not significantly influenced by macroeconomic variables, namely inflation and Bank Indonesia interest rates.